THE MAIN THOUGHTS OF THE REFORMATION OF MARTIN LUTHER AND THE CHURCH MOVEMENT AND ITS IMPLICATIONS FOR THE CHRISTIAN RELIGIOUS EDUCATION (CRE) - Udur Ernita Aritonang; Juaniva Sidharta (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study examines the main ideas of Martin Luther's Reformation, the development of the church movement, and its implications for Christian Religious Education (CRE). The Reformation, initiated by Luther in the 16th century, was not merely a reaction to the deviations of the Catholic Church, but a spiritual calling rooted in the experience of justification by faith (Romans 1:17). Luther opposed the church's abuse of indulgences and established key theological principles: Sola Scriptura, Sola Fide, Sola Gratia, Solus Christus, and Soli Deo Gloria. These principles gave rise to major changes in theology, church life, and faith education. The Lutheran movement expanded through the Augsburg Confession of 1530, which became the foundation of the teachings and identity of Protestant churches. The core of Luther's teaching, the doctrine of justification by faith, frees people from the fear of God's wrath and directs the focus of faith solely on Christ. This study uses qualitative methods with a library study, examining Luther's works and secondary literature. The results show that Luther's thoughts have had a significant impact on CHE, namely, faith education centered on Scripture, emphasizing a personal relationship with Christ, and a pedagogical vision that upholds access to education for all. The practical implication is that Christian Religious Education is called to develop a faith that is critical, reflective, and faithful to the Word, enabling students to become witnesses of Christ in society. The main ideas of Luther's Reformation remain relevant for renewing church life and Christian education today.